Selection, Salience and political identities. A constructionist approach to the political representation of ZANU-PF succession disputes in The Herald and Daily News from May 2014 to December 2014. - Masungo, Kurauone (Midlands State University, 2017)
The study critically explores the representation of Zanu-PF political disputes in The Herald and Daily News. The mentioned newspapers selectively employ the discourse of ‘weevils’ and ‘Gamatox’ in ascribing political identities to those who were regarded as locking horns in the battle to succeed the president. The study also looks at how ownership, funding and control patterns of The Herald and Daily News influenced their framing of the disputes. Data for this research was obtained through critical discourse analysis of newspaper articles published from the period May 2014 to December 2014. In-depth unstructured interviews were also conducted with editors from both The Herald and Daily News. Findings established that frames adopted by both newspapers reflect on different versions of reality advanced by both newspapers. The Herald, adopted a frame that is pro-revolutionary, that is it viewed the disputes as weeding out counter revolutionary elements. For the Daily News, the disputes were a symbol that reflects on Zanu-PF’s failure to embrace democratic values and a regime gone mad. In Chuma’s, (2008) terms The Herald and Daily News, adopted the ‘patriotic’ and ‘oppositional’ journalism models respectively.